1985
DOI: 10.1351/pac198557060833
|View full text |Cite
|
Sign up to set email alerts
|

Defects in the molecular structure of polyvinylchloride and their relation to thermal stability

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…After the reaction, the amine groups could be assigned to that of the extremity of the molecule. The PVC was choosen as host matrix for conducting phase PV-B-BA because of its high purity [11]. It has been shown that impurity could give rise to relaxation phenomenon at a more or less high frequency, or perturbs the dielectric properties of the conducting polymer [12].…”
Section: Synthesismentioning
confidence: 99%
“…After the reaction, the amine groups could be assigned to that of the extremity of the molecule. The PVC was choosen as host matrix for conducting phase PV-B-BA because of its high purity [11]. It has been shown that impurity could give rise to relaxation phenomenon at a more or less high frequency, or perturbs the dielectric properties of the conducting polymer [12].…”
Section: Synthesismentioning
confidence: 99%
“…8 Samples A1 and A2 are sample A after substitution reaction with sodium benzenethiolate (NaBT) in cyclohexanone (CH) solution up to molar conversions of 1É1% and 5%, respectively. Sample D is sample B after a substitution reaction with NaBT in the molten state up to 0É95 mol%.…”
Section: Methodsmentioning
confidence: 99%
“…Long chain branches are formed when mid chain radicals (R (6) and R (7) in Figure 2), formed by an intermolecular hydrogen abstraction, add to monomer: viz. Figure 2.…”
Section: Kinetic Modelmentioning
confidence: 99%
“…Since both radicals R (6) and R (7) result from H-abstraction reactions involving a polymer molecule, long chain branches can only be formed in the polymer-rich phase since polymer molecules that are formed in the monomer-rich phase are considered to immediately precipitate into the polymer-rich phase.…”
Section: Kinetic Modelmentioning
confidence: 99%